微卫星不稳定性类型及临床病理特征：基于1394例结直肠癌患者的标本检测 (Nan Fang Yi Ke Da Xue Xue Bao, 2020)
OBJECTIVE: To explore the clinicopathological features and types of genic mutations in DNA mismatch repair (MMR) in colorectal cancer (CRC). METHODS: Immunohistochemistry was used to determine the expression of MMR proteins in 1394 patients with CRC, and PCR-capillary electrophoresis (PCR-CE) was used to detect microsatellite instability (MSI) in 106 cases of defective MMR (dMMR), 46 cases of proficient MMR (pMMR) with heterogeneous expression and 147 randomly selected cases of pMMR. The relationship between the expressions of MMR proteins and the clinicopathological features of the patients was evaluated. The consistency between the results of immunohistochemistry and PCR-CE was assessed. RESULTS: Immunohistochemical staining showed an incidence of dMMR of 7.6% in the patients. The main type of dMMR was co-deletion of MLH1 and PMS2, accounting for 55.7% of the total dMMR cases. The deletion of MMR proteins was significantly correlated with the patients' age, tumor location, tumor size, gross type, histological type, degree of differentiation, lymph node status and TNM stage (P < 0.05), but not with gender (P > 0.05). The total accordance rate of immunohistochemistry and PCR-CE was 98.7% in these patients. CONCLUSION: The main type of dMMR is co-deletion of MLH1 and PMS2 in patients with colorectal cancer. dMMR colorectal cancer has typical clinicopathological features and a lower incidence in China than in Western countries. The results of immunohistochemistry and PCR-CE are highly consistent for detecting dMMR in colorectal cancer patients.